Coping in People Living with HIV/AIDS (PLWHA) and its Association with Depressive Disorder (Journal of Psychiatrists' Association of Nepal, 2022)
Introduction: Among PLWHA, fewer studies have done to assess the coping and their role in increasing the morbidity and mortality among people living with HIV/AIDS (PLWHA).Objective: This study aims to study coping among PLWHA and their association with depression.Methodology: This study was conducted at the outpatient HIV clinic in a tertiary center (TUTH). All relevant information was noted in a semi structured proforma designed for the study. BDI-II and brief COPE were the tools used.Result: Among the depressed and non-depressed groups, the mean scores on emotional support (and standard deviation), were found as 4.41 (1.104) and 5.32 (1.511) respectively. There is a negative correlation between depressive scores (BDI) and total score on brief COPE.Conclusion: PLWHA with lower level of depression were to found to score more on brief COPE.